Workplace Spirituality and Organisational Citizenship Behaviour: The Role of Spiritual Quotient, Intelligence Quotient and Job Satisfaction - Jasman Saripuddin Hasibuan; Azhari Akmal Tarigan; Nur Ahmadi Bi Rahmani (International Journal of Business Economics (IJBE), 2026)
Purpose – This research aims to investigate the impact of workplace spirituality and Intelligence Quotient on organisational citizenship behaviour, both directly and indirectly, through the mediating roles of job satisfaction, Spiritual Quotient, and Emotional QuotientMethodology – The study adopts a causal research design using a quantitative approach, with a sample consisting of 126 administrators and supervisors from the Indonesian Islamic Pension Fund Association. Data were collected via interviews and questionnaires, and the hypotheses were tested using Partial Least Squares (SmartPLS) analysis.Findings – Among the seven hypotheses tested, two were rejected. The findings revealed that the Spiritual Quotient did not enhance the relationship between workplace spirituality and organisational citizenship behaviour, and that the Emotional Quotient did not strengthen the connection between workplace spirituality and job satisfaction.Originality/Novelty – This study offers an integrated model that links workplace spirituality, Intelligence Quotient, Spiritual Quotient, Emotional Quotient, and job satisfaction to explain organisational citizenship behaviour within an Islamic pension fund.Implications – The findings guide managers in improving organisational citizenship behaviour by strengthening workplace spirituality, enhancing job satisfaction, and developing employees’ intellectual, spiritual, and emotional intelligence through targeted human resource practices.